2003
DOI: 10.1021/ja034115p
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystallography and Magnetic Studies of a Stable Macrocyclic Tetranitroxide. Intramolecular Dimer of Nitroxides in a Constrained Geometry of the Upper Rim of Calix[4]arene

Abstract: Synthesis, crystallography, and magnetic characterization of a stable macrocyclic tetranitroxide 1, a calix[4]arene, which is functionalized with four tert-butylnitroxides at the upper rim, is described. In solution, 1 has a 4-fold symmetric fixed cone conformation on the NMR time scale and small, but nonnegligible, exchange interactions between the radicals (30 K > /J/k/ >>1.8 mK). In the solid state, dimerization of one diagonal pair of nitroxides leads to a pinched cone conformation for 1 with strong intrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
(40 reference statements)
1
19
0
Order By: Relevance
“…[16] & [17] Recently, calix [4]arene and resorcinarene macrocycles have been adopted as scaffolds for attaching two or four organic radicals as pendants at the upper or lower rim. [20], [21], [21a], [21b], [22], [23], & [24] For example, direct attachment of radicals at the upper rim of calix [4]arenes that are constrained to an 1,3-alternate or cone conformation has provided unique models for the dissection of the through-bond and through-space intramolecular exchange coupling, as well as for the study of conformational dependence of through-bond coupling ( Figure 2). [23] & [24] The through-bond coupling between the adjacent radicals [4]arenes functionalized with in-chain radicals forming a cross-conjugated π-system: polyarylmethyl S = 2 tetraradical and polymer with magnetic ordering.…”
Section: Introductionmentioning
confidence: 99%
“…[16] & [17] Recently, calix [4]arene and resorcinarene macrocycles have been adopted as scaffolds for attaching two or four organic radicals as pendants at the upper or lower rim. [20], [21], [21a], [21b], [22], [23], & [24] For example, direct attachment of radicals at the upper rim of calix [4]arenes that are constrained to an 1,3-alternate or cone conformation has provided unique models for the dissection of the through-bond and through-space intramolecular exchange coupling, as well as for the study of conformational dependence of through-bond coupling ( Figure 2). [23] & [24] The through-bond coupling between the adjacent radicals [4]arenes functionalized with in-chain radicals forming a cross-conjugated π-system: polyarylmethyl S = 2 tetraradical and polymer with magnetic ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Macrocyclic molecules, such as cyclophanes and calixarenes, have attracted much interest because of their ability to include various guests and the possibility of forming supramolecular assemblies 1. Calixarenes functionalized by nitroxide radicals, which are widely used as stable spin sources, have been documented,2–5 revealing their peculiar properties; especially, remarkable changes in continuous‐wave (cw)‐ESR spectra with and without guests were observed 3. Calixarene‐based high‐spin entities, nevertheless, have rarely been well‐characterized, particularly in terms of their electronic‐spin properties versus their molecular structure.…”
Section: Methodsmentioning
confidence: 99%
“…Rajca et al. reported pioneering work on a calix[4]arene derivative having four nitroxide radicals in the upper (wider) rim of the calixarene skeleton 5. The X‐ray crystal structure of that calixarene derivative revealed that the two diagonally arranged radical sites formed an intramolecular dimeric structure undergoing a strong antiferromagnetic interaction.…”
Section: Methodsmentioning
confidence: 99%
“…Rajca et al reported pioneering work on a calix[4]arene derivative having four nitroxide radicals in the upper (wider) rim of the calixarene skeleton. [5] The X-ray crystal structure of that calixarene derivative revealed that the two diagonally arranged radical sites formed an intramolecular dimeric structure undergoing a strong antiferromagnetic interaction. The spin state of the derivative was only characterized from magnetic susceptibility measurements, which did not give clear and straightforward evidence for the molecular-structure-related microscopic magnetic properties of calixarene-based exchange-coupled systems.Herein, we show for the first time that nitroxide tetraradical 1 (Scheme 1) with four nitroxide radical sites in the upper rim of the calixarene skeleton is in a quintet state.…”
mentioning
confidence: 99%
“…
Macrocyclic molecules, such as cyclophanes and calixarenes, have attracted much interest because of their ability to include various guests and the possibility of forming supramolecular assemblies.[1] Calixarenes functionalized by nitroxide radicals, which are widely used as stable spin sources, have been documented, [2][3][4][5] revealing their peculiar properties; especially, remarkable changes in continuous-wave (cw)-ESR spectra with and without guests were observed. [3] Calixarene-based high-spin entities, nevertheless, have rarely been well-characterized, particularly in terms of their electronic-spin properties versus their molecular structure.
…”
mentioning
confidence: 99%